Dialog Antar Umat Beragama Sebagai Piranti Menumbuhkan Sikap Toleransi - Imas Setiyawan Setiyawan; Elfada Adella Hidayat (LPPM Institut Pesantren KH. Abdul Chalim, 2018)
Inter-religious harmony has until now become a goal in the life of every human being. Where each individual or group continues to maintain an attitude of tolerance to always live peacefully in a country that has diverse ethnic groups, customs, culture and religion. Given that tolerance must be possessed by every human being on this earth. What about mutual respect, respecting the trust of others, and not forcing the truth to those who already have their own truth. Like religious tolerance, every human being must respect the worship procedure for other religions, teachings that they believe in in his religion and do not see one's religious background if he wants to help him. Dialogue, is one way for tolerance to be maintained in interfaith relations. With the dialogue between religious people, whether individuals or religious groups, it will be easier to express their thoughts without fear of arousing words of attacking one another. In every religion, such as Islam, Christianity, Buddhism, Hinduism, and Confucianism, views on tolerance and dialogue between religious groups are different. Although, it has the same meaning. Namely, both of them aim to continue to maintain the harmony of life between religious people. In this article, we will discuss interfaith dialogue, tolerance and dialogue in the perspective of religions. Also how can dialogue be a moral to foster an attitude of enthusiasm among religious people.